1999
DOI: 10.1093/bja/82.5.746
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic management of epidermolysis bullosa

Abstract: Epidermolysis bullosa is the name given to a group of rare, genetically determined diseases characterized by cutaneous blistering and subsequent scarring. It presents a challenge to the anaesthetist managing patients who often require multiple operations. This review article includes a retrospective audit of cases treated at St Thomas' Hospital between 1993 and 1998. We studied the case notes and anaesthetic records of patients with dystrophic epidermolysis bullosa requiring anaesthesia and recorded the anaest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
97
1
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 17 publications
0
97
1
3
Order By: Relevance
“…However, its use in patients with DEB has not been widely described in the literature. Ames et al [7] reported it to be safe in patients with epidermolysis bullosa, although in one patient a single new lingual bulla formed. The present patient had a history of multiple episodes of oral bulla formation with rupturing and scarring; thus, we considered tracheal intubation a safer method of airway management than the use of a laryngeal mask airway.…”
Section: Discussionmentioning
confidence: 99%
“…However, its use in patients with DEB has not been widely described in the literature. Ames et al [7] reported it to be safe in patients with epidermolysis bullosa, although in one patient a single new lingual bulla formed. The present patient had a history of multiple episodes of oral bulla formation with rupturing and scarring; thus, we considered tracheal intubation a safer method of airway management than the use of a laryngeal mask airway.…”
Section: Discussionmentioning
confidence: 99%
“…However, ketamine is contraindicated in the presence of hypertension, myocardial insufficiency, psychiatric disorders, or raised intracranial pressure. Also, excitation during recovery may cause further trauma [7]. Thiopentone and propofol have also been used for induction and maintenance of anesthesia [5,7].…”
Section: Discussionmentioning
confidence: 99%
“…Also, excitation during recovery may cause further trauma [7]. Thiopentone and propofol have also been used for induction and maintenance of anesthesia [5,7]. Brachial plexus [1], spinal, and epidural [7,8] blocks in EBD patients have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations